Analisis Literatur: Pendidikan Islam sebagai Pondasi Moralitas dalam Masyarakat - Dwi Yuliana; Cyrilla Salsabilla Athaya P; Sultania Intan Faradis; Mu’alimin Mu’alimin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Islamic education plays a strategic role in shaping the morality of individuals and society. Based on the teachings of the Qur'an and Sunnah, Islamic education not only delivers religious knowledge but also builds Islamic character rooted in the values of tauhid (oneness of God), hablum minallah (relationship with God), and hablum minannas (relationship with others). This study analyzes literature to explore the relevance of Islamic education in addressing the challenges of modernization and globalization. The findings show that Islamic education remains crucial as a foundation of morality by integrating spiritual, social, and technological values into the learning process. Active learning methods like PAKEM have proven effective in enhancing students' moral understanding, while communities play a vital role in supporting the success of value-based Islamic education. The main challenge is to keep Islamic education relevant by adapting to social changes, technological advancements, and local and global needs. Therefore, collaboration among educators, educational institutions, and society is essential to sustain Islamic education as a strong moral foundation in the modern era.